Risk management process into project lifecycle: a case of Malaysia landscape architecture projects - S.Muthueeran, Adam Aruldewan; Mohd Tahir, Osman; Ibrahim, Roziya; Abd-Karim, Saipol Bari (e-International Publishing House, 2020)
The risk management process is an integral part of all project activities and proportionally customized as one process. This paper prepared to review risk management process integration into the landscape architecture project lifecycle in Malaysia. Data collected from three completed landscape architecture projects studied through structured interviews and project document reviews. The data analyzed using content and thematic analysis. The study found the ineffective risk management process integration into the project lifecycle with the result of the incomplete, unplanned and intended process, and redundant activity ow. Specific integration strategies recommended accommodating landscape architecture project context for practical risk management applications.